MODERN MODEL FORMATION OF DRUG PROVISION OF PATIENTS WITH COMMUNITY-ACQUIRED PNEUMONIA IN KABARDINO-BALKARIA - A. A. Umirova; V. L. Adzhienko; T. I. Kabakova; E. A. Korzhavykh; V. V. Gatsan (Фармация и фармакология (Пятигорск))
The increase in the incidence of community-acquired pneumonia (СAP) is a major problem of national and regional importance. Its pharmacotherapy is based on the active use of antibacterial drugs. That requires a special attention of both, a doctor and a patient, the search for all new and advanced medicines (drugs).The aim of the study is to justify and develop a regional model of drug provision of pharmacotherapy in community-acquired pneumonia.Materials and methods. The use of the resource approach and the methodology of pharmaceutical care (PhC) for the formation of a modern model of drug supply have been tested. Logical, retrospective, sociological, pharmacoeconomic, marketing, statistical and other analytical methods have been used. The materials were official statistics, literature data and the results of the research carried out by the authors themselves.Results. The state and tendencies of development of organizational, personnel, financial (population) and drug resources as the external factors affecting PhC to patients with CAP in the Kabardino-Balkarian Republic (KBR) have been identified. The following internal factors of PhC have been defined: medical prescriptions, consumer demands and the cost of pharmacotherapy. A model of drug provision for patients with CAP in the region has been formed. It is aimed at increasing the effectiveness of treatment, taking into account the stage of treatment and the price factor.Conclusion. Under the conditions of a particular region, the use of the resource approach and the PhC methodology allows to more accurately identify the problems and risks of both drug provision and pharmacotherapy of the patients’ population under study, and form a model adequate to reality, develop recommendations for all participants of PhC – a doctor, a patient and a pharmaceutist (a pharmacist).